2D Quantitative Structure Activity Relationship Studies on Structurally Constrained Quinazoline Derivatives as Potent and Selective Histamine H3 Receptor Inverse Agonists - Singh, Mahaveer; Kumar, Sunny (Asian Journal of Chemistry, 2012)
In the present study 2D quantitative structure activity relationship (QSAR) study was performed on a new series of novel structurally constrained quinazoline derivatives for their H3 receptor inverse agonistic activity. This series is reported by Tsuyoshi and Takashi. 2D quantitative structure activity relationship study was performed by using JChem. for Excel (version 5.3.6). Multiple linear regression analysis was performed, which was further evaluated with training and test set of compounds for prediction of activity. Several statistical regression expressions were obtained using multiple linear regression analysis. Matrix was used to evaluate each parameter for its contribution. R value was found 0.975 and correlation coefficient Rsqr was found 0.9567. The study indicated that topological parameters (Balaban index, harary index), thermodynamic descriptors (refractive index, dreiding energy) and topological parameter (Balaban index) and log P etc. play important role for the histamine receptor inverse agonistic activity.